Atmospheric oxidation chemistry and ozone production: Results from SHARP 2009 in Houston, Texas. Issue 11 (7th June 2013) - Ren, Xinrong; van Duin, Diana; Cazorla, Maria; Chen, Shuang; Mao, Jingqiu; Zhang, Li; Brune, William H.; Flynn, James H.; Grossberg, Nicole; Lefer, Barry L.; Rappenglück, Bernhard; Wong, Kam W.; et al.
Abstract : [1] Ozone (O3 ) and secondary fine particles come from the atmospheric oxidation chemistry that involves the hydroxyl radical (OH) and hydroperoxyl radical (HO2 ), which are together called HO x . Radical precursors such as nitrous acid (HONO) and formaldehyde (HCHO) significantly affect the HO x budget in urban environments. These chemical processes connect surface anthropogenic and natural emissions to local and regional air pollution. Using the data collected during the Study of Houston Atmospheric Radical Precursors (SHARP) in spring 2009, we examine atmospheric oxidation chemistry and O3 production in this polluted urban environment. A numerical box model with five different chemical mechanisms was used to simulate the oxidation processes and thus OH and HO2 in this study. In general, the model reproduced the measured OH and HO2 with all five chemical mechanisms producing similar levels of OH and HO2, although midday OH was overpredicted and nighttime OH and HO2 were underpredicted. The calculated HO x production was dominated by HONO photolysis in the early morning and by the photolysis of O3 and oxygenated volatile organic compounds (OVOCs) in the midday. On average, the daily HO x production rate was 24.6 ppbv d −1, of which 30% was from O3 photolysis, 22% from HONO photolysis, 15% from the photolysis of OVOCs (other than HCHO), 14% from HCHO photolysis, and 13% from O3 reactions with alkenes. The O3 production was sensitive to volatile organic compounds (VOCs) in the early morning but was sensitive to NO x for most of afternoon. This is similar to the behavior observed in two previous summertime studies in Houston: the Texas Air Quality Study in 2000 (TexAQS 2000) and the TexAQS II Radical and Aerosol Measurement Project in 2006 (TRAMP 2006). Ozone production in SHARP exhibits a longer NO x ‐sensitive period than TexAQS 2000 and TRAMP 2006, indicating that NO x control may be an efficient approach for the O3 control in springtime for Houston. Results from this study provide additional support for regulatory actions to reduce NO x and reactive VOCs in Houston in order to reduce O3 and other secondary pollutants. Key Points: The model reproduced the measured OH and HO2 with all five chemical mechanisms. HOx production was dominated by HONO photolysis in the early morning. P(O3) was VOC sensitive in the morning and NOx sensitive for most of afternoon.